Reading Comprehension by using Assemblr for Young Learner in 6th Grade Students of SDIT AL Irsyad - -, Hilman; Umalihayati; Abdul Muin Bahaf; Nia Kurniawati; Nuraeni; Dewi Setya Ningrum; Fakhira Anisa Maharani; Putri Solihatunnisa (English Education Department, 2023)
This study aims to (1) analyze students' reading comprehension using Assemblr media; (2) find out whether this media can foster students' interest in reading. The approach in this research is descriptive qualitative, the subject of this research is 17 students of the 6th grade students of SDIT Al Irsyad Banten. Data were obtained from tests, questionnaires, and interviews. In the learning process, Assemblr is used as a medium or tool for displaying teaching materials. This teaching material is in the form of a story entitled